Effect of Foliar Applications of Humic Acid, Iron and Zinc on some Characteristics of Negro (Guizotia abyssinica L.) - Ali Tadayyon; Sedigheh Beheshti (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī, 2016)
One of the most important needs in farm planning is the evaluation of different systems of plant nutrition. By supplying the correct way of plant nutrition you can preserve the environment and increase efficiency of agricultural inputs. In order to investigate the effect of foliar application of organic fertilizers and micronutrients on some characteristics of neger, a field experiment was conducted in a complete randomized block design with three replications at Agricultural Research Station of Shahrekord University in 2013-2014. Treatments consisted of control, three levels of humic acid (1, 3, and 6 liters/ha of humic acid, iron (4 per thousand), and zinc (4 per thousand). In this experiment traits like plant height, stem diameter, stem branch number, biological yield, seed yield, harvest index, and percent and oil yield were evaluated. The results showed that foliar application of these materials resulted in significant increase in the traits under study. Oil yield increased by 63 and 53 percent with the use of 6 liters humic acid and zinc respectively, as compared to the use of 1 liter per hectare. This may be the outcome of increased in oil yield and protein content. Meanwhile, the highest percentage of protein observed for tratment of 6 liters per hectare. The highest response of traits firstly obtained by use of 6 liters per hectare humic acid and then from spraying plants with the zinc which shows its limited absorption and/or probably the lack of this element in the soil where the experiment was conducted.